Globalization and the Responsibility of the Intellectual (II) - Mickūnas, Algis (Sociologija. Mintis ir veiksmas, 2008)
The question of intellectual responsibility in confrontation with globalization is the philosophical question from Socratic to modern philosophies. In brief, it is impossible to practice philosophy and not to raise this question. It is well known that Socrates stood his ground unto death with the demand that he and others have a duty to interrogate all claims to truth regardless of their origin. Intellectual honesty was for him a requirement to keep open the discursive domain – called the polis – wherein the search for truth could be pursued. This means that the task of philosophy as such is identical with the maintenance of an open polis wherein all theories and propositions can be tested and contested. Hence, when we raise the question of the responsibility of the intellectual, we must recall the task for philosophy set by Socrates. Yet our situation is quite different from that of classical Athens. We are confronted by modern philosophy in its ontological and metaphysical guises that require a serious consideration whether we can even think of the relationship between intellectual and responsibility. It is our task, then, to consider what sort of position will open up for an intellectual that would be worthy of philosophy.
Keywords: globalization; intellectuals; responsibility; modern identity; multiplicity of discourses